THE URGENCE OF THE ROLE OF SPIRITUAL LEADERSHIP ON INTRINSIC MOTIVATION AND ORGANIZATIONAL COMMITMENT AND THEIR IMPACT ON JOB SATISFACTION - Agus Sugiardi (Assyarikah: Journal of Islamic Economic Business, 2021)
The purpose of this study was to determine the effect of spiritual leadership on intrinsic motivation, the effect of spiritual leadership on organizational commitment, the effect of intrinsic motivation on job satisfaction, the effect of organizational commitment on job satisfaction, and the effect of spiritual leadership on job satisfaction. This research is classified as explanatory research with a quantitative approach. The sample used was 130 employee at Regional General Hospital of Pamekasan Regency with purposive sampling technique. The type of data used is primary data, namely collecting data using questionnaires. Analysis of the data used is SEM. The results of this study indicate that Spiritual leadership has a positive and significant effect on intrinsic motivation, Spiritual leadership has a positive and significant effect on organizational commitment, Intrinsic motivation has a positive and significant effect on job satisfaction, Organizational commitment has a positive and significant effect on job satisfaction, and Spiritual leadership has a significant positive effect on job satisfaction.